Evaluasi Penerapan Sistem Informasi Manajemen Rumah Sakit di Bagian Rekam Medis Rumah Sakit Bhayangkara POLDA DIY - Piping Asgiani; Andi Karisma Nurdiyansyah (Universitas Jenderal Achmad Yani Yogyakarta, 2022)
Background: RS Bhayangkara POLDA DIY is one of any hospital who used SIMRS since 2011, but in fact they never do any evaluating which very important to the goods for the hospital itself.Objective: To evaluate the implementation of SIMRS in the medical records section of the Bhayangkara POLDA DIY Hospital.Methods: The data was collected by observation, interview, and documentation. Research population are all of 6 medical record employees, and the sample is from all of those 6 employees.Results: The performance and information aspects are considered not good, the economic, control, efficiency, and service aspects are considered good. The user's satisfaction, it has been considered good but there are still obstacles faced by the user, namely the system performance is not optimal, system error and network are slow.Conclusion: The hospital should follow up this complain from user and coordinate with IT officer for optimizing the system as soon as possible